Address Space Layout Randomization (ASLR) in Windows & Linux: Proof of Concept (PoC) Implementation - Sonawala, Dipam (My University, 2013)
ASLR is a computer security method which involves randomly arranging the positions of key data areas, usually including the base of the executable and position of libraries, heap, and stack in a process's address space. This work analyses trends in software security through an investigation of buffer overflow security strategies.
ME Thesis, Master of Engineering (CSE)
Keywords: Buffer Overflow; ASLR